The Intelligent Architecture of Healthcare: How AI Leverages Medical Knowledge Graphs - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2023)
The convergence of Artificial Intelligence AI and healthcare is rapidly transforming diagnostics, treatment planning, and drug discovery. At the heart of thi...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation